Koi Herpesvirus (KHV) Disease - Kathleen H. Hartman; Roy P. Yanong; Deborah B. Pouder; B. Denise Petty; Ruth Francis-Floyd; Allen C. Riggs (EDIS, 2008)
Revised! VM-149, a 9-page illustrated fact sheet by Kathleen H. Hartman, Roy P.E. Yanong, Deborah B. Pouder, B. Denise Petty, Ruth Francis-Floyd, and Allen C. Riggs, informs veterinarians, biologists, fish producers and hobbyists about the KHV disease in a question-and-answer format. Includes glossary and references. Published by the UF College of Veterinary Medicine, October 2008.